Analisis Pembentukan Portofolio Optimal Saham-Saham JII30 Dengan Model Indeks Tunggal Periode New-Normal - Miftahul Huda; Syarif Abdullah; Sri Istiyarti Uswatun Chasanah; Himmatul Mursyidah; Fajri Ikhsan; Sidik Susilo; Rani Septiani Sukandar (Pendidikan Matematika Universitas PGRI Yogyakarta, 2022)
The purpose of this research is to analyze the formation of the optimal portfolio on the Jakarta Islamic Index 30 (JII30) stocks during the new normal period. The model used is a single index model. This study uses secondary data for the period December 2020 - November 2021 from stocks listed on JII30 on the Indonesia Stock Exchange. The results showed that the selected model provides optimal benefits. The risk-free asset return does not provide a higher return than the simulation results. Of the 30 stocks listed in JII30, obtained 7 stocks with the most significant proportion of funds, namely ERAA (25.72%), MDKA (24.87%), TLKM (17.98%), EXCL (12.82%), AKRA (7.54%), ADRO (6.73 %) and ANTM (4.34%). The formation of the optimal portfolio in this study produces an expected return of 0.009974 or 1%, where the portfolio return is above the market rate of return and the average risk-free rate. Meanwhile, the optimal portfolio risk obtained is 0.003173 and the standard deviation is 0.056327 or 5.63%. The impact of the Covid-19 pandemic which has subsided and the economy is getting better has resulted in the formation of an optimal JII30 portfolio that can be carried out and reduce investment risk during the new normal period.Â Keywords: Jakarta Islamic Index 30 (JII30), Single Index model, new normal, Optimal portfolio